Biomarkers and Nutrients in Musculoskeletal Disorders - Calvo-Lobo, César; de Bengoa Vallejo, Ricardo Becerro; Losa-Iglesias, Marta Elena; San-Antolín, Marta; Sanz, David Rodríguez; López-López, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The present Special Issue summarizes the available scientific evidence concerning the nutrients and biomarkers in musculoskeletal diseases linked to the metabolic conditions secondary to COVID-19 confinement, osteoporosis prevention for patients with inflammatory bowel diseases, and the nutritional status in patients with spinal muscular atrophy. Furthermore, it explores the novel findings for experimental animal models of pharmacological agents to improve the regeneration of muscle tissue; acetylcholine spontaneous release located in the neuromuscular junction in mice, secondary to hypercaloric diet supplementation with an increase in spontaneous neurotransmission and the activation of myofascial trigger points associated with myofascial pain syndrome; and myogenic biomarkers in musculoskeletal conditions and gene expression associated with vitamin D and L-cysteine co-supplementation. This Special Issue is edited by a multidisciplinary group comprising the Universidad Complutense de Madrid, Universidad Rey Juan Carlos, Universidade da Coruña, and Universidad Europea de Madrid.